Video‐assisted thoracoscopic treatment of primary spontaneous pneumothorax in older children and adolescents. Issue 7 (8th April 2016) - Ciriaco, Paola; Muriana, Piergiorgio; Bandiera, Alessandro; Carretta, Angelo; Melloni, Giulio; Negri, Giampiero; Fiori, Rossana; Zannini, Piero
Summary: Background: Primary spontaneous pneumothorax (PSP) is a relatively rare condition in the pediatric population lacking of specific recommendations regarding the management. Video‐assisted thoracoscopic surgery (VATS) has gained widespread consensus during the last 10 years. We retrospectively reviewed our experience of VATS in the treatment of pediatric patients affected by PSP in terms of timing of surgery, operative technique, and postoperative outcome. Methods: Between 1998 and 2014, 58 pediatric patients were treated for PSP. Treatment consisted in pulmonary apicectomy in all patients and pleurodesis. Patients received either apical pleurectomy and mechanical pleurodesis or mechanical pleurodesis alone. Results: Mean age was 16.6 ± 1.6 years (range 10–18) with a male/female ratio of 5:1. Seventeen patients underwent surgery after the first episode of PSP. Apical pleurectomy and mechanical pleurodesis was performed in 30 patients while others received mechanical pleurodesis alone. Conversion to open surgery was needed in four procedures (6.9%). Postoperative complications occurred in 1.7% of cases. Sixteen patients received more than one procedure for contralateral pneumothorax (15 cases) and postoperative recurrence (1 case). The mean follow‐up was 95 ± 63 months. Recurrence rate was 12.1%. Univariate analysis showed that recurrence was significantly correlated with younger age ( P  = 0.044) and postoperative chest tube ( P  = 0.027). Both univariate and multivariate analysis showed that apical pleurectomy did not prevent recurrences. Conclusions: VATS is an effective procedure for PSP in pediatric patients. Apical pleurectomy does not seem to prevent recurrence. Due to the increased risk of recurrence of PSP in younger patients, indication to VATS after the first episode might be considered.Pediatr Pulmonol. 2016;51:713–716 . © 2016 Wiley Periodicals, Inc.